Ontologies in radiation oncology. (April 2020) - Phillips, Mark H.; Serra, Lucas M.; Dekker, Andre; Ghosh, Preetam; Luk, Samuel M.H.; Kalet, Alan; Mayo, Charles
Highlights: Description of ontologies for medical uses. Examples of ontology applications in radiation therapy. Ontologies as basis for communication protocols. Efforts by American Association of Medical Physicists to construct an ontology. Abstract: Ontologies are a formal, computer-compatible method for representing scientific knowledge about a given domain. They provide a standardized vocabulary, taxonomy and set of relations between concepts. When formatted in a standard way, they can be read and reasoned upon by computers as well as by humans. At the 2019 International Conference on the Use of Computers in Radiation Therapy, there was a session devoted to ontologies in radiation therapy. This paper is a compilation of the material presented, and is meant as an introduction to the subject. This is done by means of a didactic introduction to the topic followed by a series of applications in radiation therapy. The goal of this article is to provide the medical physicist and related professionals with sufficient background that they can understand their construction as well as their practical uses.